2017
DOI: 10.4103/jfmpc.jfmpc_190_17
|View full text |Cite
|
Sign up to set email alerts
|

Silent changes of tuberculosis in Iran (2005-2015): A joinpoint regression analysis

Abstract: Introduction and Aim:Tuberculosis (TB) poses a severe risk to public health through the world but excessively distresses low-income nations. The aim of this study is to analyze silent changes of TB in Iran (2005–2015): A joinpoint regression analysis.Materials and Methods:This is a trend study conducted on all patients (n = 70) that register in control disease center of Joibar (one of coastal cities and tourism destination in Northern Iran which was recognized as an independent town since 1998) during 2005–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In our study, 48.1% of patients were elderly (60 years age and older); the highest incidence of TB in the study by Khazaee et al in Hamadan province during 2005 to 2011 was over 60 years (20). So, TB incidence has shown strong age association (23). Even mean age TB cases of Sunnetcioglu et al in Turkey (24) and Atif et al in Pakistan (25) were less than 40 years.…”
Section: Discussionmentioning
confidence: 41%
“…In our study, 48.1% of patients were elderly (60 years age and older); the highest incidence of TB in the study by Khazaee et al in Hamadan province during 2005 to 2011 was over 60 years (20). So, TB incidence has shown strong age association (23). Even mean age TB cases of Sunnetcioglu et al in Turkey (24) and Atif et al in Pakistan (25) were less than 40 years.…”
Section: Discussionmentioning
confidence: 41%
“…In 2021, the largest number of new cases of TB was found in Southeast Asia with 46% of new cases, followed by Africa with 23% of new cases, and the Western Pacific with 18%. Globally, the incidence of tuberculosis is falling, but not fast enough to reach the 2020 milestone of a 20% reduction between 2015 and 2020 [ 27 ]. Glaziou et al reported a decreasing trend in the incidence, prevalence, and mortality rate of tuberculosis in the world between 1990 and 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the Iranian Ministry of Health reports, the total incidence of tuberculosis in Iran decreased by 1.17% between 2005 and 2015, while it increased by approximately 4% in Mazandaran province [ 27 ]. A study conducted in the west of Iran (Kurdistan province) showed that the incidence rate has been decreasing during the years 2000–2012 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that the frequency of extrapulmonary TB was higher than pulmonary TB (63.5 and 36.5%, respectively). However, a different result had been reported from Iran, as 71.4% of the patients had pulmonary TB [30]. Other studies had found different rates of extrapulmonary TB, including 49.4% in Turkey [31], 39.1% in southern Ethiopia [16], and 21% in the Netherland [32].…”
Section: Discussionmentioning
confidence: 96%